Evolution of rapidly grown cellular microstructure during heat treatment of TiAl-based intermetallic and its effect on micromechanical properties. (May 2021) - Liu, Shiqiu; Ding, Hongsheng; Chen, Ruirun; Guo, Jingjie; Fu, Hengzhi
Abstract: Continuous growth of rapidly grown cellular microstructure (i.e., cellular microstructure obtained by rapid solidification) could be realized by the method of laser powder bed fusion. However, there is still lack of research about how to adopt post heat treatment further optimizing this type of homogeneous and fine microstructure. Herein, the phase and microstructure evolution of rapidly grown cellular microstructure of TiAl-based intermetallic during heat treatment was specifically investigated; besides, both the micromechanical properties and behavior of the heat-treated microstructures were analyzed. The phase and microstructure evolution of Ti–48Al–2Cr–2Nb (in at.% unless otherwise specified) rapidly grown cellular microstructure during heating at 694–1180 °C was: the α2 rapidly grown cellular microstructure transformed into cellular microstructure with α2 /γ nanolamellae substructures at 694 °C; at 900 °C, almost all of the rapidly grown cellular microstructure transformed into γ phase, and began to transform into equiaxed microstructures by recrystallization; when the temperature increased to 936 °C, α2 phase began to be precipitated in or between the equiaxed γ grains; after being held at 1000 °C for 30 min, the rapidly grown cellular microstructure completely decomposed into equiaxed near-γ microstructures. The nanohardness of the heat-treated microstructures first decreased then increased with increasing heat-treatment temperature, the maximum nanohardness (8.697 GPa on average) was obtained after heat treatment at 700 °C. The cellular microstructure with nanolamellae substructures can further improve the strength and toughness of the rapidly grown cellular microstructure, effectively realizing the strengthening and toughening of TiAl-based alloy. Highlights: Phase and microstructure evolution after heat treatments of a TiAl rapidly grown cellular microstructure was studied. Micromechanical properties of rapidly solidified and heat-treated samples were characterized. After being held at 1000 °C for 30 min, the rapidly solidified material completely decomposed into near-γ microstructures. Cellular microstructures with nanolamellae substructures can further improve the strength and toughness.